2021
DOI: 10.1016/j.arth.2021.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Abductor Muscle Strength Deficit in Patients After Total Hip Arthroplasty: A Systematic Review and Meta-Analysis

Abstract: Background: The aims of this study were to assess and quantify hip abductor muscle strength deficits after total hip arthroplasty (THA) and to determine associations with external factors. Methods: Studies reporting on hip abductor muscle strength before and/or after THA performed for osteoarthritis or atraumatic osteonecrosis of the hip were considered for inclusion. Data sources were Embase, Medline, and the Cochrane Central Register of Controlled Trials. Muscle strength on the affected side was compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Recovery of muscle strength ( e.g. , quadriceps and hip abductors)—which coincides with this period ( Mizner, Petterson & Snyder-Mackler, 2005 ; Ismailidis et al, 2021 ) –may underly these improvements in walking capacity. As for trunk kinematics, both individuals after TKA and THA showed an increase in lumbar coronal RoM from two to fifteen months after surgery, which may relate to the restored ability of the hip abductors to control frontal plane pelvic movement ( Bolink et al, 2016 ; Reininga et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of muscle strength ( e.g. , quadriceps and hip abductors)—which coincides with this period ( Mizner, Petterson & Snyder-Mackler, 2005 ; Ismailidis et al, 2021 ) –may underly these improvements in walking capacity. As for trunk kinematics, both individuals after TKA and THA showed an increase in lumbar coronal RoM from two to fifteen months after surgery, which may relate to the restored ability of the hip abductors to control frontal plane pelvic movement ( Bolink et al, 2016 ; Reininga et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the pelvic alignment, the implant position, and other confounding factors were not assessed in this study. Whereas femoral offsets could influence hip abductor strength after THA [27], a recent study has shown that alterations in acetabular and femoral offsets after THA have no effect on postoperative gait function [28]. Fourth, it remains uncertain whether patients with bilateral symptomatic osteoarthritis or severe hip deformity may show similar results.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we evaluated MRI at 1 year postoperatively, and we were unable to track MRI changes beyond that time. Ismailidis et al [14] stated that hip abductor muscle weakness might gradually improve during the first 24 months after THA. It is possible that M-CSA atrophy and fatty atrophy in MRI may resolve in the future when MRI is followed for more than one year.…”
Section: Discussionmentioning
confidence: 99%